Sport As A Tool For Building Political Alliances: The Olympics Of EmergingPowers (GANEFO) - Nugroho Saputro, Imron; Tandiyo Rahayu; Soedjatmiko; Sulaiman (Universitas Negeri Semarang, 2025)
This study examines the Games of New Emerging Forces (GANEFO) as a dynamic sporting event. It examines and analyzes that GANEFO is not just an international sporting event, but also a product of foreign political competition and a contest of diplomatic relations between foreign countries. This study uses a historical research method. The implementation of GANEFO in November 1963 is often associated with international political practices after World War II. The feud between the Western Bloc and the Eastern Bloc triggered the holding of the Asia Africa Conference. The spirit of the Non-Aligned Movement was adopted by Indonesia to mobilize other countries to participate in GANEFO. In addition, the influence of the PRC as an exponent of a communist state also played an important role in the success of GANEFO in Jakarta. At the national level, the long feud between Soekarno, political parties, and the military elite also encouraged the implementation of GANEFO during the Guided Democracy era. Competition between domestic camps triggered Soekarno to try to take a superior position by organizing an international-scale sporting event. This method was used by Soekarno to attract public sympathy while simultaneously dwarfing the position of his domestic competitors. Thus, holding sports competitions can be used as an instrument to untangle the complexities of diplomatic relations and domestic political disputes.